Development of Human Digestive System Teaching Aids with a Social Phenomenology Approach to Improve Learning - Lestiavita, Meisa; Agustin, Nurul; Rahmat Rudianto (Universitas Terbuka, 2025)
Education plays an important role in forming a quality generation, one of which is through learning Natural Sciences (IPA) in elementary schools. However, the material on the human digestive system is relatively abstract and difficult for students to understand if it is only delivered through lecture methods. This study aims to develop human digestive system teaching aids with a social phenomenology approach to improve the learning outcomes of fifth grade students of MI Darul Ulum Driyorejo Gresik. The method used is research and development (R&D) with the 4-D model from Thiagarajan which includes the stages of define, design, develop, and disseminate. The development procedure begins with needs analysis, product design using used materials, expert validation, media revision, and limited trials. The results of the study showed that the teaching aids developed received very positive responses from students (83%) and teachers (88%). In addition, there was an increase in learning outcomes from 75% in the pretest to 98% in the posttest. This shows that the developed digestive system teaching aids are effective in helping students' understanding and are suitable for use in the science learning process in elementary schools.